Security in a greater Europe : The possibility of a pan-European approach - Wagnsson, Charlotte (Book collections on Project MUSE., 2008)
This book contrasts the EU's new way of 'doing security' with the established, competitive bilateral interplay in the European security sphere and provides a clue to the kind of security politics that will prevail in Europe. A joint Moscow Brussels approach would improve the chances of both increasing their relative strength vis-à-vis the USA, but serious cleavages threaten to undermine such a 'greater European' common view on security.